Bacterial response to Ti-35Nb-7Zr-5Ta alloy incorporated with calcium, phosphate and magnesium - dos Reis, Bárbara Araújo [UNESP]; Da Ponte Leguizamón, Natalia [UNESP]; Del Rey, Yumi Chokyu; Fernandes, Leandro [UNESP]; do Nascimento, Cássio [UNESP]; Vaz, Luis Geraldo [UNESP] (Springer Nature, 2023)
High implant survival rates have been achieved in recent decades due to continual modifications in implant design and surface topography, however there is still an ongoing quest to control peri-implant bone loss. The objective of this work was to develop Ti-35Nb-7Zr-5Ta (TNZT) alloys, perform physicochemical and morphological characterization of their surface modified by electrolytic oxidative plasma technique with ions related to osseointegration and lastly evaluate bacterial colonization in vitro. Three groups were evaluated: C group (polished TNZT), CaP group (sodium β glycerophosphate + calcium acetate) and Mg group (magnesium acetate). Before and after anodizing the surfaces, physicochemical and morphological analyses were performed: scanning electron microscopy with field emission gun (FEG-SEM), energy dispersion spectroscopy (EDS), X-ray diffraction (DRX), wettability (goniometer) and roughness (rugometer). Controlled and treated specimens were contaminated with unstimulated saliva collected from 10 healthy volunteers. Then, biofilm samples were collected and up to 35 microbial species, including commensal and pathogenic microorganisms, were identified and quantified by the Checkerboard DNA-DNA Hybridization method. The CaP group modified the surface morphology in the form of pores, while the Mg group modified it in the form of flakes. The contact angle was significantly smaller in the CaP group. The average roughness was higher in the CaP and Mg groups. A smaller total amount of bacteria was identified in the Mg group and relevant differences were found in the microbial profile associated with different surface treatments. Therefore, considering the microbiological profile and for the prevention of peri-implantitis, the Mg group presented more satisfactory and encouraging results for the manufacture of dental implants Graphical Abstract: [Figure not available: see fulltext.].